Emerging from a PleurX Draining Catheter: An Unexpected Diagnosis - Hasan Arafat; Hamza A Abdul-Hafez; Ali Sabateen (Clinical Medicine Insights: Case Reports)
Introduction: Ascaris lumbricoides is a common helminthic infection characterized by fecal-oral route of transmission. Commonly, it affects the gastrointestinal tract. However, in significantly rare cases, it can affect unexpected body regions, such as biliary tree, pancreas, and the lung. Case presentation: A 68-year-old female patient underwent PleurX tube insertion due to malignant pleural effusion. On the third week of insertion, she complained of itching and pain at the site of insertion, a grayish-white worm was visualized at the insertion site. Ascaris lumbricoides was identified by microbiological examination. She received 400 mg of albendazole. Conclusion: Our case describes a rare clinical situation of pleural ascariasis, emphasizing the importance of remaining aware of this rare complication of ascariasis.